Labor Market Developments in the Republic of Armenia - Galstyan, Amalya (Bulletin of Yerevan University G: Economics, 2025)
Effective functioning of the labor market is one of the keys to sustainable development and economic growth. Thus, corresponding government policy along with the other socio-economic regulation mechanisms have direct impact not only on the rate of employment and unemployment, but the other labor market indicators and as a result, on economy as a whole. The article explains the situation on the labor market of the Republic of Armenia, by investigating main indicators and the reasons of tension situation, as well as presents recommendation on improving it. In particular, it’s recommended to tighten collaboration among universities and the business, by creating specialized training programs, by improving technical and vocational education (TVE), by developing labor market institutions and implementing appropriate policy.